A parasite through time: Revisiting Trypanosoma rajae Laveran and Mesnil, 1902 with new molecular and morphological insights from the blood of Rajidae in the western Mediterranean - Sabrina Kefil; Linda Duval; Amandine Labat; Chahinez Bouguerche; Nadia Kechemir-Issad (International Journal for Parasitology: Parasites and Wildlife)
Trypanosomes are blood parasitic protozoa infecting Chordates, including the elasmobranch skates (Rajidae). Amongst, Trypanosoma rajae Laveran and Mesnil, 1902 is a century old parasite, first briefly described from the Mediterranean starry ray Raja asterias and the undulate ray R. undulata off Roscoff, France, Northeast Atlantic, for which illustrations and molecular data are still lacking. Herein, we investigate blood trypanosomes of R. asterias, type-host of T. rajae and of those from the blood of the brown ray R. miraletus, collected off the Algerian coast, Western Mediterranean. We describe these trypanosomes using an integrative taxonomic approach combining morphological characters and partial 18S rRNA gene sequencing, and we provide several morphological, morphometrical, anatomical and biological characteristics (division stages). Specific characteristics of Trypanosoma ex R. asterias such as granulations of the nucleus and cytoplasm; shape of the kinetoplast, nucleus and body; tip of the body; the undulating membrane, as well as the morphometric measurements were within the ranges given in the previous records of T. rajae, and we ascribe thus the newly collected trypanosomes from R. asterias to T. rajae. Algeria and the Western Mediterranean are new locality records for T. rajae. Trypanosomes ex R. miraletus differed from T. rajae ex R. asterias by some morphometrical data: posterior end to kinetoplast (PK), free flagellum length (FF), the kinetoplast index (KI), slenderness (Sle), flagellar index (FI), mid-nucleus to anterior end (NA) and parasite maximum body width at nucleus (BWN). Partial 18S rRNA gene sequences of T. rajae ex R. asterias and Trypanosoma sp. ex R. miraletus showed ∼99.76 % similarity. We take a conservative position and refer to trypanosomes from R. miraletus as T. cf. rajae. Phylogenetic analysis using 18S rRNA gene sequences of other aquatic trypanosomes allowed positioning of T. rajae relative to the other trypanosome species, previously described, infecting marine and freshwater hosts worldwide. Some divisional stages were also observed on MGG-stained thin smears allowing a brief description of the division of this trypanosome in the blood of its host. This effort is the first study of T. rajae using integrative taxonomy combining morphology and DNA and we provide for the first time observations of dividing stages of this species in the host blood.